(untitled) (Revista de Medicina Clinica, 2017)
Sudden cardiac death (SCD) is one of the biggest challenges not only of modern cardiology, but also of modern society and can be considered along with infant mortality an indicator of general population health, this article it emphasizes on the causes of sudden cardiac death including new diseases that 10 years ago were not yet known and therefore are subdiagnosticated and underrated; besides generalities quickly review the symptoms and the most current treatment in MSC.Rev Med Clin 2017;1(1)30-39.